The "Design Thinking" Hadith and its Relevance to Creative Economy Activities in Metro Lampung City: “Design Thinking” Hadits dan Relevansinya dengan Kegiatan Ekonomi Kreatif di Kota Metro Lampung (Takwil: Journal of Quran and Hadith Studies, 2024)
One of the problems that exist in society today is the creative economy which is an alternative to strengthening the economy. The results of the Creative Economy Survey in 2020, the largest contributor to Indonesia's GDP is the Fashion Culinary Products and Crafts subsector. In line with the contribution of the creative economy to national economic growth, if traced back to the time of the Prophet SAW when he was in Medina, the efforts he made after political affairs and conditions were completed, he began to pay attention to the economy. community growth, by encouraging people to utilize existing natural resources and reactivating markets to revive buying and selling activities. The activities he carried out in order to improve the community's economy are documented through his words, including the idea of a creative economy that began to develop at that time. This paper explores the concept of creative economy in Hadith and discusses the Prophet's Hadith as an inspiration for creative economic activities in Metro City. This article collects field data with a qualitative descriptive approach. The research location in this study is the Creative Economy Market in Metro City, namely Tejo Agung Creative Market (Pak Tejo) and Yosomulyo Pelangi Market (Paungi).